5 and 7 Year Old Childrenwith No English Background RespondToward Parentsâ Stimulus Using the Comprehensible Inputs on Direct English Daily Conversations at Home - Rini, Setia (State Institute of Islamic Studies Salatiga, 2008)
This paper seeks to explorehow the comprehensible inputs are given by motherÂ Â responded by the children who have no English background and what are the discourse features which aid childrenâs comprehension and ability to maintain the conversation. This study is conducted in the writerâs home with her sons in order to apply the comprehensible inputs. The results shows that the children ages 5 and 7 years old who have no English background are able to give the responses unless the questions or the stimulus given must be followed by the non verbal language such as gesture and the body movements. In this case, the results can be varied. From the stimulus using the comprehensible inputs, the children are also giving different responses. It can be in the form of non-verbal language such as nodding or by repeating the last word said by their mother. It is suggested that parents should give encouragement to the children and help them in acquiring the second language at home.Â Keywords:Â Parentsâ stimulus; Comprehensible inputs; daily conversation with no English background.